Evaluation of Fungicides and Biocontrol agents against Fusarium wilt of Tomato - Majid, Abdul; Ahmed, Nadeem; Tariq, Hasaan; Qayyum, Mirza Abdul (Journal of Agriculture and Biology, 2024)
Tomato (Solanum lycopersicum L.) belonging to Solanaceae family is a chief component of daily food. It is cultivated by market gardeners as well as for kitchen gardening. It is largely produced in Punjab Sindh and KPK province in Pakistan. Fusarium oxysporum f. sp. lycopersici is the significant soil-borne pathogen causing fusarium wilt in tomato. In Pakistan, yield is reduced by 21.9% due to tomato wilting. The fusarium wilt of tomato was managed by using different fungicides and bio-control agents. Tomato seeds were sown in trays followed by transplanting. Fungicides; Score (Difenoconazole) at dose of 0.3 ml/L, 2 g/L Topsin-M (Thiophanate methyl) and biocontrol agents (Trichoderma spp. and Bacillus sp. at concentrations of 1×103 and 1×103 spore/ml) were applied after inoculating the transplanted plants with disease inoculum. Treatments were applied after a week of tomato seedling transplant. Using disease rating scales, disease severity symptoms and disease incidence were recorded at weekly intervals. Collected data was analyzed. First symptoms of the disease were appeared after 8 days of disease inoculation. The result indicated that after application of treatments, in controlled pots T0 showed maximum disease of 32.64% which was recorded after spraying with distilled water. Minimum disease was recorded in that plants whích was sprayed by Trichoderma spp. (9.52%) and Bacillus spp. (12.41%) were found most effective against fusarium wilt of tomato. The fungicide sprays; Difenoconazole (25.43%) were least effective then biocontrol sprays. Thiophanate methyl (18.91%) was given fair result among other chemical. In present study, results of Trichoderma spp. and Bacillus spp. applications revealed that all the other three treatments were significantly superior over control in managing the Fusarium disease spread. Among all sprays, T3 and T4 were significantly superior over other treatments. With the exception of all treatments, that were found superior in action over T0 (control). The overall results showed that T3 (Trichoderma sp.) was most effective against fusarium wilt of tomato. Thus, use of biocontrol agents were most effective and at the same time it is environment friendly. This study will be fruitful for the farmers to manage these soil-borne pathogen that will lead to high production of tomato.
Keywords: Fusarium wilt; Tomato; Biological control; Fungicides; Sustainable agriculture